Sixteen weeks of resistance training can decrease the risk of metabolic syndrome in healthy postmenopausal women - Conceição MS (Dove Medical Press, 2013)
Miguel Soares Conceição,1 Valéria Bonganha,1 Felipe Cassaro Vechin,2 Ricardo Paes de Barros Berton,1 Manoel Emílio Lixandrão,1 Felipe Romano Damas Nogueira,1 Giovana Vergínia de Souza,1 Mara Patricia Traina Chacon-Mikahil,1 Cleiton Augusto Libardi2 1Exercise Physiology Laboratory, School of Physical Education, State University of Campinas, Campinas, 2Laboratory of Neuromuscular Adaptation to Strength Training, School of Physical Education and Sport, University of São Paulo, São Paulo, Brazil Background: The postmenopausal phase has been considered an aggravating factor for developing metabolic syndrome. Notwithstanding, no studies have as yet investigated the effects of resistance training on metabolic syndrome in postmenopausal women. Thus, the purpose of this study was to verify whether resistance training could reduce the risk of metabolic syndrome in postmenopausal women. Methods: Twenty postmenopausal women were randomly assigned to a resistance training protocol (n = 10, 53.40 ± 3.95 years, 64.58 ± 9.22 kg) or a control group (n = 10, 53.0 ± 5.7 years, 64.03 ± 5.03 kg). In the resistance training protocol, ten exercises were performed, with 3 × 8–10 maximal repetitions three times per week, and the load was increased every week. Two-way analysis of variance was used to evaluate specific metabolic syndrome Z-score, high density lipoprotein cholesterol, fasting blood glucose, triglycerides, waist circumference, blood pressure, strength, and body composition. The level of statistical significance was set at P < 0.05. Results: The main results demonstrated a significant decrease of metabolic syndrome Z-score when the postmenopausal women performed resistance training (P = 0.0162). Moreover, we observed decreases in fasting blood glucose for the resistance training group (P = 0.001), and also significant improvements in lean body mass (P = 0.042, 2.46%), reduction of body fat percentage (P = 0.001, −6.75%) and noticeable increases in muscle strength after resistance training to leg press (P = 0.004, 41.29%) and bench press (P = 0.0001, 27.23%). Conclusion: It was concluded that resistance training performed three times a week may reduce the metabolic syndrome Z-score with concomitant decreases in fasting blood glucose, improvements in body composition, and muscle strength in postmenopausal women. Keywords: metabolic syndrome, resistance training, postmenopausal women